Parallel Optical Window Algorithm Applied to Optical Multistage Interconnection Network - Othman, Mohamed; Abdullah, Monir; Johari, Rozita (Institute for Mathematical Research, 2008)
The crosstalk problem is introduced in an optical multistage interconnection network caused by coupling two signals within a switching element. To avoid this crosstalk, a time domain approach is used, which is to partition the set of permutation connections into several subsets such that the connections in each subset can be established simultaneously in the network without crosstalk. Since we want to partition the messages to be sent to the network into several groups, we have to use the window method that is used for finding the conflicts among all the messages to be sent. In this paper, a new parallel algorithm of the window method is developed called the Balanced Parallel Window Method (BPWM) algorithm. The BPMW algorithm reduces the execution time by a percentage of 83% of the time compared to the sequential algorithm with seven processors.